2012
DOI: 10.1289/ehp.1104405
|View full text |Cite
|
Sign up to set email alerts
|

The Greening of Pesticide–Environment Interactions: Some Personal Observations

Abstract: Background: Pesticide–environment interactions are bidirectional. The environment alters pesticides by metabolism and photodegradation, and pesticides in turn change the environment through nontarget or secondary effects.Objectives: Approximately 900 currently used commercial pesticides of widely diverse structures act by nearly a hundred mechanisms to control insects, weeds, and fungi, usually with minimal disruption of nature’s equilibrium. Here I consider some aspects of the discovery, development, and use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 90 publications
0
27
0
Order By: Relevance
“…69 Following absorption into the body, pesticides are often biotransformed to water-soluble metabolites for the purpose of detoxification and elimination. Rates of biotransformation can be rapid (hours to days), as in the case of OP insecticides, or extremely slow (years to decades), as is noted for OC insecticides, which accounts for the bioaccumulation of these lipophilic compounds in adipose tissue.…”
Section: Mechanisms Of Pesticide Toxicitymentioning
confidence: 99%
“…69 Following absorption into the body, pesticides are often biotransformed to water-soluble metabolites for the purpose of detoxification and elimination. Rates of biotransformation can be rapid (hours to days), as in the case of OP insecticides, or extremely slow (years to decades), as is noted for OC insecticides, which accounts for the bioaccumulation of these lipophilic compounds in adipose tissue.…”
Section: Mechanisms Of Pesticide Toxicitymentioning
confidence: 99%
“…The use of synthetic pesticides leads to many ecological problems. The most important negative impacts include ecological imbalance, high toxicity, residues in soil and water that affect human and animal health (Casida 2012;Roberts & Karr 2012), and the resistance of Culex against insecticides (Gordon & Ottea 2012). It was found that Culex populations could develop resistance on account of the widespread use of insecticides (Jones et al 2012).…”
mentioning
confidence: 99%
“…In the 1980s, based on mass, pesticide use declined somewhat because of the scaling back of pesticide overuse and the introduction of compounds that are used at lower concentrations (23). For example, the OP-chlorinated hydrocarbon chlorpyrifos, which was introduced in 1965, is typically applied in orange orchards at 2.9 kg active ingredient (a.i.)/ha.…”
Section: Trends In Pesticide Use With An Emphasis On Us Agriculture mentioning
confidence: 99%
“…In comparison, in the global north, mass of pesticide applied decreased from 1.8 kg a.i./ha to 1.6 kg a.i./ha, but the decrease is accounted for at least partly by substitution of materials that are toxic to the target organisms at lower concentration. However, many of the newer pesticides are also less toxic to nontarget organisms, although there are exceptions, such as with the toxicity of the neonicotinoid imidacloprid to honeybees and the toxicity of the herbicide paraquat (introduced in 1962) to mammals and birds (23). As a fungicide example, the older fungicide captan has a lethal dose to 50% of the population (LD 50 ) in fish of 0.034 to 0.3 ppm, whereas the newer strobilurin azoxystrobin has an LD 50 of 0.47 to 1.6 ppm (156), i.e., azoxystrobin has greater selective toxicity but remains a potential threat to aquatic environments, particularly because it has a half-life in soil of 70 days, in comparison to 1 day for captan (133,156).…”
Section: Trends In Pesticide Use With An Emphasis On Us Agriculture mentioning
confidence: 99%